2022
DOI: 10.3390/biom12060859
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Transcriptome in the Hearts Isolated from Mice, Rats, and Humans

Abstract: The heart is a significant organ in mammalian life, and the heartbeat mechanism has been an essential focus of science. However, few studies have focused on species differences. Accordingly, challenges remain in studying genes that have universal functions across species and genes that determine species differences. Here, we analyzed transcriptome data in mouse, rat, and human atria, ventricles, and sinoatrial nodes (SA) obtained from different platforms and compared them by calculating specificity measure (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…After functional validation, we confirmed consistency in our RNA sequencing across sample pools by conducting principal component analysis and examining the expression of known positive (Shox2, Isl1, Tbx3, Hcn4, Flrt3, Lsps1) and negative (Nkx2.5, Scn5a, Bmp10, Gja5) markers of CPCs (Hoogaars et al, 2004(Hoogaars et al, , 2007Blaschke et al, 2007;Espinoza-Lewis et al, 2009;Wiese et al, 2009;Bakker et al, 2012;Ye et al, 2015aYe et al, , 2015bIonta et al, 2015;Liang et al, 2015Liang et al, , 2020Bressan et al, 2018;Li et al, 2019;van Eif et al, 2019;Thomas et al, 2021;Okada et al, 2022). Marker gene expression analysis indicated that all three sample pools showed similar fold differences in previously identified differentially expressed genes (Fig S1B ) and principal component analysis demonstrated strong separation between SAN and atrial sample pools (Fig S1C).…”
Section: Cpc Architecture Changes Over the Course Of San Morphogenesismentioning
confidence: 62%
See 1 more Smart Citation
“…After functional validation, we confirmed consistency in our RNA sequencing across sample pools by conducting principal component analysis and examining the expression of known positive (Shox2, Isl1, Tbx3, Hcn4, Flrt3, Lsps1) and negative (Nkx2.5, Scn5a, Bmp10, Gja5) markers of CPCs (Hoogaars et al, 2004(Hoogaars et al, , 2007Blaschke et al, 2007;Espinoza-Lewis et al, 2009;Wiese et al, 2009;Bakker et al, 2012;Ye et al, 2015aYe et al, , 2015bIonta et al, 2015;Liang et al, 2015Liang et al, , 2020Bressan et al, 2018;Li et al, 2019;van Eif et al, 2019;Thomas et al, 2021;Okada et al, 2022). Marker gene expression analysis indicated that all three sample pools showed similar fold differences in previously identified differentially expressed genes (Fig S1B ) and principal component analysis demonstrated strong separation between SAN and atrial sample pools (Fig S1C).…”
Section: Cpc Architecture Changes Over the Course Of San Morphogenesismentioning
confidence: 62%
“…Indeed, the atypical microarchitecture present in the SAN has garnered significant interest over the last 100 years ( Opthof, 1988 ; Shiraishi et al, 1992 ; Csepe et al, 2015, 2016 ; Ho & Sá nchez-Quintana, 2016 ; Kalyanasundaram et al, 2019 ). State-of-the-art transcriptional and proteomic profiling have begun to reveal the diversity and specialization of the ECM present in the mature SAN ( Liang et al, 2015 ; Vedantham et al, 2015 ; Gluck et al, 2017 ; Li et al, 2019 ; Linscheid et al, 2019 ; van Eif et al, 2019 ; Brennan et al, 2020 ; Kalyanasundaram et al, 2021 ; Mandla et al, 2021 ; Minhas et al, 2021 ; Okada et al, 2022 ) which has given rise to the hypothesis that the mechanical properties of the SAN microenvironment may be important for overall CPC function ( Gluck et al, 2017 ; Linscheid et al, 2019 ; Kalyanasundaram et al, 2021 ). However, this model has not been empirically tested and few data are available to assess how local biomechanics influence CPC activity.…”
Section: Introductionmentioning
confidence: 99%
“…In DE analysis, if gene expression levels differ significantly between diseased and non-diseased donors, then the genes are considered to be associated with that disease. Similarly, a comparison of gene expression data from different tissues or anatomical regions can therefore be used to identify tissue/region-specific genes [5] , [6] , [7] . Expression quantitative trait locus analysis (eQTL) can be used to identify genetic variants in genotype groups that are significantly associated with gene expression levels, and in so doing, can facilitate an understanding of the mechanisms underlying gene regulation and interpretations of functional genetic variants [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to elucidate the mechanism of cardiac function, Dr. Namekata et al and Dr. Okada et al employed a strategy of comparing different animal species [ 4 , 5 ]. To our knowledge, the normal beating heart is driven by a coupled-clock system in which Ca 2+ release preceding the action potential is reflected in depolarization via a Na + –Ca 2+ exchanger (NCX).…”
mentioning
confidence: 99%
“…Similarly, Dr. Okada et al dismissed the high-scoring report stating that Tbx18 is the most critical transcription factor that characterizes pacemaker cells [ 8 ]. They reported that SHOX2 is the essential transcription factor for pacemaker cells when animal species, including humans, are considered [ 5 ].…”
mentioning
confidence: 99%